Magnetic droplet solitons in orthogonal spin valves - Chung, Sunjae; Mohseni, S. Majid; Eklund, Anders; Dürrenfeld, Philipp; Ranjbar, Mojtaba; Sani, Sohrab R.; Nguyen, T. N. Anh; Dumas, Randy K.; Åkerman, Johan (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
We review the recent experimental advancements in the realization and understanding of magnetic droplet solitons generated by spin transfer torque in orthogonal nanocontact based spin torque nanooscillators (STNOs) fabricated on extended spin valves and spin valve nanowires. The magnetic droplets are detected and studied using the STNO microwave signal and its resistance, the latter both quasistatically and time-resolved. The droplet nucleation current is found to have a minimum at intermediate magnetic field strengths and the nature of the nu-cleation changes gradually from a single sharp step well above this field, mode-hopping around the minimum, and continuous at low fields. The mode-hopping and continuous transitions are ascribed to droplet drift instabil-ity and renucleation at different time scales, which is corroborated by time-resolved measurements. We argue that the use of tilted anisotropy fixed layers could reduce the nucleation current further, move the nucleation current minimum to lower fields, and potentially remove the need for an applied magnetic field altogether. Finally, evidence of an edge mode droplet in a nanowire is presented.